Cannabidiol in canine epilepsy. (December 2022) - Potschka, Heidrun; Bhatti, Sofie F.M.; Tipold, Andrea; McGrath, Stephanie
Abstract: The anticonvulsant effect of cannabidiol (CBD), which has been confirmed by findings from animal models and human trials, has attracted the interest of veterinary practitioners and dog owners. Moreover, social media and public pressure has sparked a renewed awareness of cannabinoids, which have been used for epilepsy since ancient times. Unfortunately, at this moment veterinarians and veterinary neurologists have difficulty prescribing cannabinoids because of the paucity of sound scientific studies. Pharmacokinetic studies in dogs have demonstrated a low oral bioavailability of CBD and a high first-pass effect through the liver. Administering CBD in oil-based formulations and/or with food has been shown to enhance the bioavailability in dogs, rats and humans. Tolerability studies in healthy dogs and dogs with epilepsy have demonstrated that CBD was safe and well tolerated with only mild to moderate adverse effects. In this context, it should be noted that the quality of available CBD varies widely, underscoring the importance of pharmaceutical quality and its control. One clinical trial in dogs with drug-resistant idiopathic epilepsy failed to confirm a difference in response rates between the CBD group and the placebo group, while in another cross-over trial a ≥ 50 % reduction in epileptic seizure frequency was found in six of 14 dogs in the treatment phase, a reduction that was not observed during the placebo phase. Based on the current state of knowledge it is not possible to provide clear-cut recommendations for the use of CBD in canine epilepsy. Randomized controlled canine trials with large sample sizes are needed to determine the range of therapeutic plasma concentrations, develop evidence-based dosing regimens, determine the efficacy of cannabidiol in drug-refractory epilepsy, and explore potential associations between treatment effects and different etiologies, epilepsy types, and drug combinations. Highlights: Cannabidiol can exert antiseizure effects in rodents and human patients. Cannabidiol doses used in canine studies are well tolerated. Oral bioavailability is influenced by pharmaceutical formulations and food intake. Efficacy in canine drug-refractory epilepsy has been assessed in two studies. Large canine clinical studies are necessary to conclude about therapeutic potential.